Haematopoietic stemcell transplantation in Kariadi General Hospital Semarang Indonesia - Setyowati, Sri; Rakhmawati, Anik; Susilowati, Ari (Sahabat Publikasi Kuu, 2023)
In Indonesia, bone marrow transplantation is a treatment which not known yet to some people. Kariadi Hospital is the one hospital that do it first. On 1987, it was successful for acute myeloid leukemia case. Bone marrow transplantation is one of therapy used to treat patients with leukemia, severe aplastic anemia, Hodgkin's disease, non-Hodgkin's lymphoma, myeloma multiple, many blood disorder and solid tumor. This study described the patients characteristics who did hematopoietic stem cell transplantation during 2017-2021 at Kariadi General Hospital Semarang. This study is a quantitative research non-experiment with design retrospective analysis. Data was taken with a total sampling are 20 patients. Data analysis by describing the criteria. The results describe the sex of patients consist are 60% male and 40% female. Most range age at 35-44 years amount 30%. The diagnosis is 40% in the case of Myeloma Multiple. Most of transplantation doing an autologous transplant are 80%. It is indicated 90% of malignancy cases. All patient got 100% engraftment, all patients happen neutropenia, thrombocytopenia, oral mucositis, gut disorder, and electrolyte imbalance. Amount 15% are hematuria and 10% are urticaria, Veno Occlusive Disease, sepsis, brain infection and brain hemorrhage. The conclusion is patients who did hematopoietic stem cell transplantation have various adverse events and complications depending on many factors or comorbids. These are age, sex, diagnosis, stage of disease, state of remission, regiment conditioning. Health professionals should upgrade knowledge and skill for treatment of hematopoietic stem cell transplantation.